Executive Function Training in Childhood Obesity: Food Choice, Quality of Life, and Brain Connectivity (TOuCH): A Randomized Control Trial Protocol - Sanchez-Castañeda, Cristina; Luis-Ruiz, Sandra; Ramon-Krauel, Marta; Lerin, Carles; Sanchez, Consuelo; Miró, Núria; Martínez, Sònia; Garolera, Maite; Jurado, Maria Angeles (Frontiers in Pediatrics, 2021)
Background: Individuals with obesity are known to present cognitive deficits, especially in executive functions. Executive functions play an important role in health and success throughout the whole life and have been related to food decision-making and to the ability to maintain energy balance. It is possible to improve executive functions through targeted training. This would involve brain plasticity changes that could be studied through connectivity magnetic resonance imaging. The general hypothesis of this study is that executive functions training in children with obesity can improve food choices and produce cognitive and neuroimaging changes (structural and functional connectivity), as well as improve emotional state and quality of life. Methods: randomized controlled double-blind trial with 12-months follow-up. Thirty children with obesity will be randomly allocated into ‘executive training’ (Cognifit with adaptive difficulty + Cogmed) or ‘control task’ group (Cognifit without adaptive difficulty). Both groups will attend 30-45 minutes of individual gamified training (Cogmed and/or Cognifit systems) by iPad, 5 times per week during 6 weeks. Cogmed and Cognifit software are commercially available from Pearson and Cognifit respectively. Participants will receive an iPad with both apps installed for a 6-week use. Participants will also receive counselling diet information via presentations sent to the iPad and will wear a Fitbit Flex 2 tracker to monitor daily activity and sleep patterns. Main outcomes will be cognitive, emotional, food decision and quality of life measures, as well as neuroimaging measures. Participants are evaluated at baseline (T0), after treatment (T1) and 12-months since baseline (T2). Discussion: Longitudinal study with active control group and 3 time points: baseline, immediately after treatment and 1 year after baseline. Three-fold treatment: Executive function training, psychoeducation, and feedback on activity/sleep tracking. We will evaluate the transfer effects of the intervention, including emotional and functional outcomes, as well as the effects on neural plasticity by connectivity MRI. Trial registration: This project has been registered in ClinicalTrials.gov (Trial registration number: NCT03615274) the 3rd of August, 2018.